Cesarean Hysterectomy for Placenta Previa Accreta Using Retrograde Abdominal Hysterectomy Approaching from the Posterior Vaginal Wall - Hiramatsu, Yuji (The Surgery Journal, 2021)
Hysterectomy for placenta percreta with bladder invasion is a difficult operation because of the high possibility of massive bleeding; therefore, surgery should be performed in a facility equipped with a sufficient number of trained staff. The degree of bladder invasion should be assessed correctly before the operation, and it is necessary to carefully consider how to address intraoperative complications and massive bleeding in the preoperative conference. The following should be prepared preoperatively: autologous blood and stored blood; ureteral catheter and insertion materials; materials to separate and tape the internal iliac artery and ureter; balloon for insertion into the common iliac artery or aorta and aortic clamps; and materials for compression suturing, such as B-Lynch suture. Sufficient informed patient consent is also required. During surgery, which may cause massive and sometimes life-threatening bleeding, the general rule is to begin at a safe site without adhesions and then treat the adhesion site. According to this rule, bladder dissection should be performed last in cases of placenta percreta with bladder invasion. As a surgical technique using this principle, we introduce retrograde hysterectomy approaching from the posterior vaginal wall.
Keywords: cesarean hysterectomy; placenta previa accreta; bladder invasion; retrograde abdominal hysterectomy; posterior vaginal wall